THE REALIZATION OF LEGISTATIVE MEASURE OF THE RIGHTS OF THE CHILD POST-SECOND AMANDEMENT OF THE CONSTITUTION - Rasyid, M Nur (Faculty of Law, Universitas Sebelas Maret, 2018)
The government has obligation to protect the rights of the child. In the second amendment of Indonesian Constitution of 1945 in 2000 it was added one chapter, namely Chapter XA on human rights. The rights of the child is incorporated in the Article 28B that stipulated every child entitles to life, growth, develop and to get protection from violence and discrimination.The problem is how the legislative measure of the rights of the child as the implementation of Article 28B. The data were obtained through library research consist of acts related to protection and judiciary of the rights of the child and the related conventions.The result of the research shows that the government has undertaken legislative measures by making act on child protection, Act Number 23 of 2002 on child protection that has been revised as Act Number 35 of 2014, and the second revision by Act Number 17 of 2016 following the Government Regulation substituted Act Number 1 of 2016. Act Number 3 of 1997 has been revised on Child Judiciary become Act Number 11 of 2012 on Child Criminal Justice System. It needs synchronization of various related regulations and capacity building for the institutions of child protection.